2019
DOI: 10.3168/jds.2019-16416
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime pasture access: Comparing the effect of production pasture and exercise paddock on milk production and cow behavior in an automatic milking system

Abstract: went to the barn and did not return to the pasture area during the remaining night. As the season progressed and nights became longer, cows on the exercise paddock treatment reduced time spent outdoors and grazing time, whereas they increased time spent resting outdoors. The group on exercise paddock had a greater milk yield (kg of milk) over the experimental period than the production pasture group. The latter group also showed a greater drop in milk yield over the duration of the trial. Thus, for cows milked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(58 reference statements)
0
6
0
1
Order By: Relevance
“…This indicates that pasture is preferred and implies that not all of pasture’s welfare benefits are transferable to more intensive production systems. Restricted pasture access, as in our study, may be a practical alternative [26,73]. Using the Welfare Quality ® assessment protocol for dairy cattle [120], Wagner et al [13] identified many of the same advantages for cows with 6–12 h of pasture per day as for cows with >12 h per day.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This indicates that pasture is preferred and implies that not all of pasture’s welfare benefits are transferable to more intensive production systems. Restricted pasture access, as in our study, may be a practical alternative [26,73]. Using the Welfare Quality ® assessment protocol for dairy cattle [120], Wagner et al [13] identified many of the same advantages for cows with 6–12 h of pasture per day as for cows with >12 h per day.…”
Section: Discussionmentioning
confidence: 64%
“…Cows in the PAS treatment had 18 h of daily pasture access, from approximately 16:00 (post-afternoon milking) until 10:00 the next morning. This covered the main grazing times (dawn and dusk [26,73,79,80]) and is when cattle choose to access pasture [24,25,26,27,30,31]. PAS cows were managed in a rotational grazing system, so the treatment groups were kept on different pastures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when a nutritionally balanced diet is provided with less variability and higher precision, producers are able to extract the full potential of their animals [ 131 ]. The diet of these animals is highly controlled, and consists of energy rich foods, such as concentrated feed, corn silage, grass, and soy cuts, amongst others [ 132 , 133 ].…”
Section: Milk Production: From Rearing To Milkingmentioning
confidence: 99%
“…La reducción del uso del ensilado es un recurso de gran importancia que se puede emplear a la hora de minimizar los costos asociados a la alimentación bovina. Este proceso se debe realizar asegurando un acceso a los forrajes durante las horas de la tarde e, incluso, en las noches (Kismul et al, 2019). El acceso a las pasturas se puede realizar en horas restringidas, delimitando así este proceso y suministrando el concentrado en el resto del tiempo, lo que puede también aumentar la eficiencia del pastoreo (Kennedy et al, 2009).…”
Section: Segunda Estrategiaunclassified